Optimization of aqueous aerosol extract (AqE) generation from e-cigarettes and tobacco heating products for in vitro cytotoxicity testing. (15th December 2020) - Bozhilova, Stela; Baxter, Andrew; Bishop, Emma; Breheny, Damien; Thorne, David; Hodges, Paul; Gaça, Marianna
Graphical abstract: Highlights: Novel nicotine products assessed in endothelial cells using cytotoxicity assay. Standardized method for aqueous aerosol extract generation. Quality control checks for batch-to-batch consistency and aerosol capture. Optimized product-by-product assessment approach. Methods suitably sensitive for inter- and intra-product category comparisons. Abstract: Electronic cigarettes (e-cigarettes) and tobacco heating products (THPs) have reduced yields of toxicants and have recently emerged as a potentially safer alternative to combustible cigarettes. To understand if reduced toxicant exposure is associated with reductions in biological responses, there is a need for high-quality pre-clinical in vitro studies. Here, we investigated the cytotoxic response of human umbilical vein endothelial cells to conventional cigarette aqueous aerosol extracts (AqE) and highly concentrated AqEs from e-cigarettes (two generations of atomisers) and THPs (two variants). All AqE samples were generated by a standardized methodology and characterized for nicotine, propylene glycol and vegetable glycerol. The cigarette AqE caused a maximum 100 ± 0.00 % reduction in cell viability at 35 % dose (2.80 puffs) as opposed to 96.63 ± 2.73 % at 50 % (20 puffs) and 99.85 ± 0.23 % at 75 % (30 puffs) for the two THP variants (glo Bright Tobacco, glo Rich Tobacco), and 99.07 ± 1.61 % at the neat ePen2.0 e-cigarette (200 puffs). The AqE of the remaining e-cigarettes either resulted in an incomplete dose-response or did not elicit any response. The methods utilized were suitably sensitive to not only differentiate between cigarette, THP and e-cigarette aerosols but also to distinguish between products within each product category.